Incidence and Risk Factors for Proximal Junctional Kyphosis: Results of a Multicentric Study of Adult Scoliosis. Issue 3 (April 2018) - Sebaaly, Amer; Sylvestre, Clément; El Quehtani, Yehya; Riouallon, Guillaume; Larrieu, Daniel; Boussiere, Louis; Steib, Jean Paul; Roussouly, Pierre; Wolff, Stéphane; Obeid, Ibrahim
Abstract : Study Design: This was a retrospective multicentric study. Objective: The objective of this study was to determine the different risk factors for development of proximal junctional kyphosis (PJK) in patients with adult scoliosis. Summary of Background Data: This study was conducted as the reasons for development of PJK in adult scoliosis are still not clear. Materials and Methods: In total, 314 patients met the inclusion criteria. The main outcome measure was the PJK, as described by Glattes and colleagues. Extent of the instrumentation, operative time, bleeding, and the use of an osteotomy as well as the type of proximal anchorage were collected. Radiologic variables included preoperative Cobb angles of the lumbar and the thoracic curvatures, pelvic parameters, lumbar lordosis, thoracic kyphosis, and sagittal vertical axis. All measures were performed using the KEOPS software. Results: The mean follow-up of this series was 2.5 years with a female to male ratio of 6.6/1 and a mean age of 56.66 years. The incidence of PJK was 25%. Proximal fixation extended to the proximal thoracic spine (TS) in 39%, to the middle TS in 39.5% of cases, and to the thoracolumbar junction in 20.4%, with a higher incidence of PJK noted in the first group. The proximal anchors had no effect on PJK incidence. Age as well as body mass index had a positive correlation to the incidence of PJK. The association, fusion to sacrum and fusion to the upper TS, is associated with the highest incidence of PJK. Preoperative pelvic tilt had a positive correlation with PJK occurrence. Finally, revision for PJK occurred in 2.3% of all patients and accounted for 15% of revisions. Conclusions: Increased age, as well as increased body mass index, is a risk factor for the development of PJK. The proximal extent of the construct is also shown to be a risk factor for PJK, but fusion to the sacrum is a risk factor only if fusion extends to the proximal TS. Moderate PJK was observed with undercorrection of the sagittal balance and severe PJKs with overcorrection of the sagittal balance. Level of Evidence: Level IV.